PATTERN OF RELATIONSHIP BETWEEN THE CAPITAL CITY OF THE NUSANTARA AND THE GOVERNMENT OF EAST KALIMANTAN PROVINCE - Ramdhan, Isnaeni; Rachman, Cipta Indralestari; Novratilova, Monica Ruzz (Universitas 17 Agustus 1945 Semarang, 2024)
The position of the Nusantara Capital City as the capital of the unitary state of the Republic of Indonesia in the territory of East Kalimantan Province, not only refers to Law Number 3 of 2022 concerning the National Capital City but also refers to Law Number 23 of 2014 concerning Regional Government and its amendments. The status of the Nusantara Capital City as a provincial-level regional government, as a special region, and its implementation is carried out by the Authority raises a new paradigm in the administration of regional government. The equality between the Archipelago Capital and East Kalimantan Province also has consequences in the relationship of governance in the two local governments. This paper will elaborate on the pattern of relations between the Nusantara Capital City Authority and the East Kalimantan Provincial Government, its potential implications, and solutions. Based on the literature study, it is concluded that the pattern of relations between the Nusantara State Capital Authority as a provincial-level special regional government and the East Kalimantan Provincial Government is coordination, potential problems arising from the unclear position of the Nusantara State Capital Authority as a ministerial-level special regional unit, and the implementation of unregulated government affairs such as environmental management and protection, budget management, local business development, population data on the Nusantara Capital which has implications for citizens' political rights, problem solving through the establishment of implementing regulations regarding the resolution of potential problems.